Enhanced ductility in high performance polyamides due to strain-induced phase transitions. (3rd January 2022) - Candau, Nicolas; Chenal, Jean-Marc; Lame, Olivier; Schouwink, Pascal; Michaud, Véronique; Plummer, Christopher J.G.; Frauenrath, Holger
Abstract: Copolymerizing poly(hexamethylene terephthalamide- co -isophthalamide) (PA6TI) with 40  wt % polyamide 66 (PA66) results in only minor decreases in modulus and yield stress owing to isomorphous substitution of PA6TI units by PA66 units in the PA6TI α phase, so that crystallinity is maintained in the resulting PA6TI-66 terpolymer. However, the ductility also significantly increases. This is attributed to a deformation-induced transformation of the PA6TI α phase to a disordered form of the PA66 α phase, where PA6TI units constitute defects and the chains adopt extended conformations. This phase is argued to be favored in initially amorphous PA66-rich regions and hence stabilizes interlamellar micro-necks that develop during yielding. By contrast, segregation of isophthaloyl units to the amorphous regions in PA6TI hinders strain-induced crystallization, leading to failure at significantly lower strains. Brittleness may therefore be a generic problem when comonomers are used to facilitate processing, but one that may be overcome through proper microstructural control. Graphical abstract: Image 1 Highlights: Melt compounding of PA66 and PA6TI to prepare random terpolymers PA6TI-PA66. Stress and stiffness in PA6TI-PA66 comparable to those of the semiaromatic PA6TI. Five-fold increased ductility and tensile toughness in the PA6TI-66. Strain induced transition from the PA6TI α to a disordered PA66 α phase.